Office ergonomics [ - Smith, Bo; Cuttrell, Steve; Leonard, Donald L.; Smith, Bo (SafetyMax, 2002)
Explains how our body interacts with our office environment and the equipment we use as part of our job. It shows how office and office equipment can be arranged and set up to develop a comfortable, safe and productive workplace. This programme addresses how to recognize ergonomic problems, the potential of adverse effects, and practical solutions employees can use to help deal with ergonomic problems in the office